Augmented Reality in Elementary Science Education: A Systematic Review of Inquiry-Based Learning, Challenges, and Opportunities - Bintang Ghany Wedari; Rohmani Rohmani (Institute of Multidisciplinary Research and Community Service, 2026)
Digital transformation in education demands learning innovations that can increase student engagement and understanding in a more interactive manner. In the context of science learning in elementary schools, integrating Augmented Reality (AR) into Inquiry-Based Learning (IBL) is a potential approach to support the visualization of abstract concepts and exploration-based learning activities. This study aims to analyze research trends, implementation challenges, and opportunities for AR integration in inquiry-based science learning in elementary schools using a Systematic Literature Review (SLR). The study was conducted in accordance with the PRISMA 2020 protocol for articles published between 2021 and 2025. The initial search process yielded 424 articles from the Scopus and Google Scholar databases. These were then selected based on inclusion and exclusion criteria, resulting in 10 final articles, which were analyzed using a qualitative thematic analysis approach. The results show that AR integration in IBL can improve learning motivation, conceptual understanding, and 21st-century skills of elementary school students, especially critical thinking, creativity, collaboration, and communication. In addition, AR has been proven to support every stage of inquiry learning, from orientation and conceptualization to investigation and discussion, culminating in a conclusion, through interactive visualization and a more immersive learning experience. However, the implementation of AR still faces various challenges, such as limited infrastructure, device readiness, teacher competency, and the potential to increase students' cognitive load if instructional design is not appropriate. This study confirms that the success of AR integration in inquiry-based science learning is determined not only by technological sophistication but also by the suitability of the pedagogical design to the characteristics of elementary school students. Therefore, continuous teacher training, the development of more intuitive AR applications, and adequate infrastructure support are needed to optimize the implementation of AR in elementary education. Keywords: Augmented reality, Inquiry-based learning, Elementary school science.